A Study on Fixed Point Theory in M-Metric Space - Bajracharya, Prakash Muni; Adhikari, Nabaraj (Scientific World, 2020)
In 2014, Asadi et al.1 introduced the notion of an M−metric space which is the generalization of a partial metric space and establish Banach and Kannan fixed point theorems in M− metric space. In this paper, we give a brief survey regarding the fixed point theorem for Chatterjea contraction mapping in the framework of M−metric space. We also give some examples which support the partial answers to the question posed by Asadi et al. concerning a fixed point for Chatterjea contraction mapping.